배구경기 분석프로그램의 입력정보 설정 및 기술수행의 효율성 분석: 프로배구 2018-2019 정규시즌 여자경기 중심으로 - 엄한주(Han Joo EOM); 김정아(Jung A KIM); 최형준(Hyongjun CHOI) (한국체육측정평가학회지, 2020)
The purpose of this study was two-folds a) to define and clarify the input variables being programmed in Volleyball Information System and b) to analyze and compare the skill efficiency of transition play in KOVO women’s pro volleyball. In recent years, computer applications become popular in competitive sport fields and have been widely applied to various sports for official match information as well as for performance analysis. Volleyball was one of the frontiers that introduced Computer Information System in international official games. Several programs are currently available and being used in the competitive field. However, the definition and clarification of the input variables are not consistent from one to another. This is especially so when the variables generated from a system were used and analysed for the academic purposes. As such, the meaning and interpretation of the results were unclear and incomparable among similar researches. This study proposed a specific notational criteria of input variables and refined the meaning of outcome variables being used for performance analysis. In addition, the variables generated from a system in KOVO were analysed by hierarchical log-linear method as an demonstrative example in order to investigate the effects of teams and win/lose on the transition actions of ‘Receive-Attack’ process. The analytic procedure and interpretation of results were provided in details with some suggestions for those who might use multiway frequency data produced in various sport events in years to come. KCI Citation Count: 0